Kontribusi Hamba Tuhan Terhadap Dinamika Pertumbuhan Gereja Masa Kini - Waruwu, Yamotani; Gulo, Kornelius (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2024)
AbstractThe dynamics of church growth in the modern era are influenced by various factors, including the role of God's servants. This research aims to analyze the contribution of God's servants to the growth of the church today and identify effective strategies in dealing with contemporary challenges. This research uses a literature study method, involving the collection of data from various written sources such as books, journals, and scientific articles. The results of the study show that God's servants have a crucial role in the growth of the church through spiritual leadership, biblical teaching, pastoral ministry, and involvement in social missions. In the digital era, technological adaptation in services is important. Factors that affect the effectiveness of the contribution of God's servants include the quality of leadership, teaching ability, and commitment to service. The findings imply the need for a comprehensive strategy in church growth, including increasing the use of technology, creating an inclusive environment, developing training programs for God's servants, and strengthening involvement in social services. In conclusion, optimizing the role of God's servants in various aspects of ministry makes a significant contribution to the growth of the church quantitatively and qualitatively, with adaptation to social and technological changes, as well as focusing on the development of relevant leadership and ministry is the key in encouraging the growth of the church in the modern era.